2020
DOI: 10.3389/fpls.2020.568277
|View full text |Cite
|
Sign up to set email alerts
|

Redundant and Non-redundant Functions of the AHK Cytokinin Receptors During Gynoecium Development

Abstract: The phytohormone cytokinin is crucial for plant growth and development. The site of action of cytokinin in the plant is dependent on the expression of the cytokinin receptors. In Arabidopsis, there are three cytokinin receptors that present some overlap in expression pattern. Functional studies demonstrated that the receptors play highly redundant roles but also have specialized functions. Here, we focus on gynoecium development, which is the female reproductive part of the plant. Cytokinin signaling has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Furthermore, the difference in seed yield may be related to the number of ovules that were initiated in the gynoecia. Indeed, CK promotes the activity of the placenta and regulates the ovule number and the distance between ovules ( Bartrina et al, 2011 ; Bencivenga et al, 2012 ; Cerbantez-Bueno et al, 2020 ) and AtML1 is expressed in the placenta ( Lu et al, 1996 ). Interestingly, other yield traits previously shown to be regulated by CK such as the activity of the inflorescence meristem and the duration of flowering ( Bartrina et al, 2011 , 2017 ) were not regulated by epidermal CK.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the difference in seed yield may be related to the number of ovules that were initiated in the gynoecia. Indeed, CK promotes the activity of the placenta and regulates the ovule number and the distance between ovules ( Bartrina et al, 2011 ; Bencivenga et al, 2012 ; Cerbantez-Bueno et al, 2020 ) and AtML1 is expressed in the placenta ( Lu et al, 1996 ). Interestingly, other yield traits previously shown to be regulated by CK such as the activity of the inflorescence meristem and the duration of flowering ( Bartrina et al, 2011 , 2017 ) were not regulated by epidermal CK.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that cytokinin is involved in gynoecium development [8,39,45,49,53]. Repeated exogenous applications of cytokinin (6-benzylamonopurine; BAP) to wild type inflorescences induces ectopic proliferative tissue from the replum, which has at its tip stigmatic-like characteristics (Figure 1A,I; [49]).…”
Section: Exogenous Cytokinin Induces Carpeloid Features In An Ag-dependent Mannermentioning
confidence: 99%
“…It is well known that phytohormones interact to maintain their fine-turned regulatory functions, and auxin and cytokinin are also referred to as the yin and yang of plant development. In recent years, substantial progress has been made in elucidating the molecular mechanisms of auxin and cytokinin signaling during carpel initiation and early gynoecium development (e.g., [8,26,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]).…”
Section: Introductionmentioning
confidence: 99%
“…This has been extensively reviewed in [ 22 , 34 , 35 ]. The more recent work demonstrated the AHK cytokinin receptors expressed in the gynoecium to have redundant and specialized functions in this tissue of Arabidopsis [ 38 ]. Many genes have already been studied ( Table 1 and Figure 2 ), but many more remain to be identified.…”
Section: The Transmitting Tractmentioning
confidence: 99%